2012
DOI: 10.3945/jn.112.157701
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with Cyanidin-3-O-ß-Glucoside Protects against Hypercholesterolemia-Mediated Endothelial Dysfunction and Attenuates Atherosclerosis in Apolipoprotein E–Deficient Mice

Abstract: In this study, we investigated the protective effects of the anthocyanin cyanidin-3-O-β-glucoside (C3G) on hypercholesterolemia-induced endothelial dysfunction in apoE-deficient (apoE(-/-)) mice. In the prevention study, twenty 8-wk-old male apoE(-/-) mice (n = 10/group) were fed a high-fat, cholesterol-rich diet (HCD) or the HCD supplemented with C3G (2 g/kg diet) for 8 wk. The endothelium-dependent relaxation response to acetylcholine in the aortas of the C3G-fed mice was greater compared with those fed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 34 publications
0
35
0
1
Order By: Relevance
“…After several washouts, phenylephrine (1 M) was used to produce a steady contraction, and acetylcholine (ACh, an endothelium-dependent vasodilator, 10 Ϫ9 to 10 Ϫ5 M) was added cumulatively to induce endothelium-dependent relaxation. Endothelium-independent relaxation was stimulated in aortic rings with sodium nitroprusside (SNP, an endothelium-independent nitric oxide-releasing agent, 10 Ϫ9 to 10 Ϫ5 M), and the vascular relaxation was recorded (41). Adenoviral vectors and infection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After several washouts, phenylephrine (1 M) was used to produce a steady contraction, and acetylcholine (ACh, an endothelium-dependent vasodilator, 10 Ϫ9 to 10 Ϫ5 M) was added cumulatively to induce endothelium-dependent relaxation. Endothelium-independent relaxation was stimulated in aortic rings with sodium nitroprusside (SNP, an endothelium-independent nitric oxide-releasing agent, 10 Ϫ9 to 10 Ϫ5 M), and the vascular relaxation was recorded (41). Adenoviral vectors and infection.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have focused on cyanidin-3-O-␤-glucoside (C3G), the best known and most investigated anthocyanin (13,16,45). Our previous studies have shown that dietary supplementation with C3G enhanced endothelium-dependent vasorelaxation and inhibited atherogenesis in hypercholesterolemic apoE Ϫ/Ϫ mice (41); the underlying mechanism may be associated with the induction of oxysterol efflux from endothelial cells by anthocyanin (42). Furthermore, we also reported that C3G intake significantly improved insulin sensitivity in both diet-induced and genetic animal models of type 2 diabetes (11); however, both the impact of C3G on vascular function in diabetes and the molecular mechanism that confers vascular protection are poorly understood.…”
mentioning
confidence: 99%
“…showed that cyanidin 3-glucoside reduced hyperlipidemia in rats 16 and Quin et al reported that chokeberry extracts attenuated epididymal adipose tissue accumulation in rats fed a fructose-rich diet 17 . Antiobesity properties of chlorogenic acid and proanthocyanidin, constituents of aronia phytochemicals, have also been reported 18 21 .…”
Section: Suppressive Effect Of Aronia Phytochemicals On Vis-mentioning
confidence: 99%
“…In the same year, Wang et al [163] used two treatment models to investigate the effect of C3G on endothelial dysfunction and atherogenesis in Apo E-deficient animals. In the prevention model, the animals were treated with doses of C3G (2 g/kg) and a cholesterol-rich diet during 8 weeks.…”
Section: Introductionmentioning
confidence: 99%